Critiques on Contemporary Discourse of International Human Rights Law: a Global South Perspective - Pratiwi, Cekli Setya; Listiningrum, Prischa; Al Anwary, Muhammad Anis Zhafran (Human Rights in the Global South (HRGS), 2022)
International human rights law faces various critiques among scholars such as Mutua and Posner. Mutua claims that international human rights law fails to accommodate cultural values, while Posner demands about its effectivity. Referring to Langford, this paper uses critical analytic approach to evaluate Posner’s critique and Mutua’s main thoughts. Langford counter critiques of Mutua and Posner are significant to mediate the discourses by providing current evidence. While opposing Posner and Mutua’s critiques of international human rights law, this paper supports Langford’s counter critiques because of three reasons. First, Langford's comprehension can ensure that IHRL not only accommodates individual rights but also communal rights. Second, Langford’s recent study indicates the effectiveness of international human rights law. Third, Langford develops a new optimism that social rights are justiciable although the strategic idea of integrating human rights with development still needs to be elaborated further. Therefore, it is significant to follow Langford’s suggestion to optimizing the international human rights law as the most recognized general standard to prevent human rights violation against the abusive power.